A thick semi-monolithic scintillator detector for clinical PET scanners. (12th March 2021) - Zhang, Chunhui; Wang, Xiaohui; Sun, Mingdao; Kuang, Zhonghua; Zhang, Xianming; Ren, Ning; Wu, San; Sang, Ziru; Sun, Tao; Hu, Zhanli; Yang, Yongfeng; Liu, Zheng
Abstract: Both monolithic and semi-monolithic scintillator positron emission tomography (PET) detectors can measure the depth of interaction with single-ended readout. Usually scintillators with a thickness of 10 mm or less are used since the position resolutions of the detectors degrade as the scintillator thickness increases. In this work, the performance of a 20 mm thick long rectangular semi-monolithic scintillator PET detector was measured by using both single-ended and dual-ended readouts with silicon photomultiplier (SiPM) arrays to provide a high detection efficiency. The semi-monolithic scintillator detector consists of nine lutetium–yttrium oxyorthosilicate slices measuring 1.37 × 51.2 × 20 mm 3 with erythrocyte sedimentation rate foils of 0.065 mm thickness in between the slices. The SiPM array at each end of the scintillator detector consists of 16 × 4 SiPMs with a pixel size of 3.0 × 3.0 mm 2 and a pitch of 3.2 mm. The 64 signals of each SiPM array are processed by using the TOFPET2 application-specific integrated circuit individually. All but the edge slices can be clearly resolved for the detectors with both single-ended and dual-ended readouts. The single-ended readout detector provides an average full width at half maximum (FWHM) Y (continuous direction) position resolution of 2.43 mm, Z (depth direction) position resolution of 4.77 mm, energy resolution of 25.7% and timing resolution of 779 ps. The dual-ended readout detector significantly improves the Y and Z position resolutions, slightly improves the energy and timing resolution at the cost of two photodetectors required for one detector module and provides an average FWHM Y position resolution of 1.97 mm, Z position resolution of 2.60 mm, energy resolution of 21.7% and timing resolution of 718 ps. The energy and timing resolution of the semi-monolithic scintillator detector in this work are worse than those of the segmented scintillator array detector and need to be further improved. The semi-monolithic scintillator detector described in this work reduces costs as compared to the traditional segmented scintillator array detector and reduces the edge effect as compared to the monolithic scintillator detector.